2020
DOI: 10.1016/j.ihj.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiography at term in diabetic pregnancies helps predict the adverse neonatal outcome - Results of a prospective observational study from South India

Abstract: There is sparse Indian data on whether fetal echocardiography among pregnant diabetics would be useful to predict adverse perinatal/neonatal outcome. Objectives To study fetal cardiac changes in diabetic mothers and non-diabetic controls from 24 weeks gestation until the neonatal period; correlate them with maternal glycemic control; study their implications on adverse perinatal/neonatal outcome. Methodology Prospective observational cohort study. Pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…Therefore, we evaluated cardiac measurements according to FG and PPG values as well as HbA1c. A previous study observed septal and myocardial hypertrophy in the poorly controlled diabetic group but could not reveal a statistically significant relationship between glycemic control and systolic functions 29 . Our study found a statistically moderate‐strong correlation in thickness, moderate correlation in diastolic functions, and a weak correlation with systolic functions.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Therefore, we evaluated cardiac measurements according to FG and PPG values as well as HbA1c. A previous study observed septal and myocardial hypertrophy in the poorly controlled diabetic group but could not reveal a statistically significant relationship between glycemic control and systolic functions 29 . Our study found a statistically moderate‐strong correlation in thickness, moderate correlation in diastolic functions, and a weak correlation with systolic functions.…”
Section: Discussioncontrasting
confidence: 84%
“…A previous study observed septal and myocardial hypertrophy in the poorly controlled diabetic group but could not reveal a statistically significant relationship between glycemic control and systolic functions. 29 Our study found a statistically moderate-strong correlation in thickness, moderate correlation in diastolic functions, and a weak correlation with systolic functions. These results demonstrated the association of morphological and functional changes with glycemic control and that FG was more associated with these changes than PPG.…”
Section: F I G U R Esupporting
confidence: 42%
“…However, they found that severe septal hypertrophy was linked to neonatal problems such as hypoglycemia, hyperbilirubinemia, and a NICU stay of more than 7 days. 18 Other neonatal problems were not recorded in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Some studies that had a smaller number of diabetic pregnant women presented glycemic control associated with FMH described increased IVST in the poor control group ( Table 4 ). 18 However, systematic review and meta-analysis mentioned FMH in well-controlled diabetic pregnancy. 4 …”
Section: Discussionmentioning
confidence: 99%
“…There are few research studies on the reference value of heart valve peak flow velocity. Twenty years ago, Skelton et al ( 27 ) found that the peak flow velocities of the mitral valve, tricuspid valve, aorta, and pulmonary artery had no correlation with GA and BW; however, a recent study found that the MV-E/A value of full-term infants at the age of 4–7 days is higher than that at birth ( 29 ). Our study found that AV, MV-E, and MV-E/A were positively correlated with GA, BW, and BSA, which may be related to the small sample size of the previous study.…”
Section: Discussionmentioning
confidence: 99%